2005
DOI: 10.1007/s10562-005-7428-z
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Oxidation of Ethene on Polycrystalline Palladium: Influence of the Oxidation State of the Surface

Abstract: The partial and total oxidation of ethene was studied on clean and oxidized polycrystalline Pd in a UHV high-pressure cell. The model catalyst was prepared under UHV conditions and characterized by thermal desorption and Auger and Raman spectroscopy. Starting from either a Pd or PdO surface, reaction to CO 2 is the predominant pathway, and acetic acid is the main byproduct between 453 and 523 K. The route to partially oxidized products, in particular acetic acid, is more favoured on the PdO surface, while on P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…More detailed information about the composition and further reaction of CH x overlayers was obtained in a high-pressure study by Morkel et al [22], with help of vibrational sum frequency generation (SFG) and X-ray photoelectron spectroscopy (XPS). Some of the present authors observed that polycrystalline palladium exhibits its highest selectivity for partial oxidation of ethene to acetic acid at about 423 K [23], in the temperature range where ethylidyne mainly decomposes towards surface-adsorbed carbon atoms [18]. In [23] it was also shown that a pre-treatment of the Pd surface with 6 mbar ethene at 493 K, resulting in massive surfacenear carbon accumulation, markedly enhanced the selectivity toward acetic acid.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…More detailed information about the composition and further reaction of CH x overlayers was obtained in a high-pressure study by Morkel et al [22], with help of vibrational sum frequency generation (SFG) and X-ray photoelectron spectroscopy (XPS). Some of the present authors observed that polycrystalline palladium exhibits its highest selectivity for partial oxidation of ethene to acetic acid at about 423 K [23], in the temperature range where ethylidyne mainly decomposes towards surface-adsorbed carbon atoms [18]. In [23] it was also shown that a pre-treatment of the Pd surface with 6 mbar ethene at 493 K, resulting in massive surfacenear carbon accumulation, markedly enhanced the selectivity toward acetic acid.…”
Section: Introductionsupporting
confidence: 52%
“…Some of the present authors observed that polycrystalline palladium exhibits its highest selectivity for partial oxidation of ethene to acetic acid at about 423 K [23], in the temperature range where ethylidyne mainly decomposes towards surface-adsorbed carbon atoms [18]. In [23] it was also shown that a pre-treatment of the Pd surface with 6 mbar ethene at 493 K, resulting in massive surfacenear carbon accumulation, markedly enhanced the selectivity toward acetic acid. The formation of a subsurface PdC phase has also been shown to induce improved selectivity in pentyne hydrogenation toward pentene by inhibiting bulk-to-surface hydrogen diffusion [24].…”
Section: Introductionsupporting
confidence: 52%
“…A kinetic study of ethane oxidation on PdO formed on a polycrystalline Pd foil performed recently in our group [33] has shown that on stoichiometric PdO, this reaction starts with a partial reduction of the surface towards the metallic state which is responsible for a delayed onset of the reaction. Therefore, we now focused on the behavior of the PdO phase upon a reductive treatment and, in comparison, upon a simple annealing treatment.…”
Section: Bstability Of Pdo Under Reductive and Annealing Conditionsmentioning
confidence: 99%
“…On the other hand, we shall focus on the differences in reduction by CO and decomposition in He atmosphere, respectively, in close correlation to previous experiments on ethane oxidation. [33] EXPERIMENT A high-vacuum chamber (base pressure of 10 -4 Pa) was used to prepare the SiO 2 -supported Pd catalysts. Pd particles (nominal thickness of 0.6 nm) were grown by electron-beam deposition at 623 K on vacuum-cleaved NaCl(001) single crystal surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The influence on the catalytic properties of carbon residing in the subsurface region was described previously [14][15][16]. Since these are all ex situ studies the question of stability of intermediates is an issue.…”
Section: -Pentyne Hydrogenation On Pd Based Catalystsmentioning
confidence: 99%